A Comprehensive Analysis of HAVCR1 as a Prognostic and Diagnostic Marker for Pan-Cancer - Liu, Sheng; Tang, Wenting; Cao, Jing; Shang, Mei; Sun, Hengchang; Gong, Jiao; Hu, Bo (Frontiers in Genetics, 2022)
Hepatitis A virus cellular receptor (HAVCR1) is a type-1 integral membrane glycoprotein that plays a key role in immunity and renal regeneration and is abnormally expressed in various tumor types. Nonetheless, the function of HAVCR1 in pan-cancer remains unknown. In this study, we comprehensively analyzed the expression and promoter methylation level of HAVCR1 and assessed the immune cell infiltration, correlation between stromal and immune cell admixture, CD (Cluster of Differentiation) and HAVCR1 expression and prognostic value of HAVCR1 mRNA expression in Liver hepatocellular carcinoma (LIHC) and Pancreatic adenocarcinoma (PAAD). Our results showed that HAVCR1 was overexpressed while the promoter methylation of HAVCR1 was decreased in Liver hepatocellular carcinoma and Pancreatic adenocarcinoma. HAVCR1 was associated with increased infiltration of B cells, CD8 cells, macrophages, neutrophils and Dendritic cells in Liver hepatocellular carcinoma and Pancreatic adenocarcinoma. HAVCR1 expression was positively correlated with the immune, stromal and estimate scores of Pancreatic adenocarcinoma and the stromal and estimate scores of Liver hepatocellular carcinoma. Furthermore, HAVCR1 expression was correlated with other immune molecules such as HHLA2 (Human endogenous retrovirus-H long terminal repeat-associating protein 2), CD44 and TNFRSF4 (TNF Receptor Superfamily Member 4) in Liver hepatocellular carcinoma and Pancreatic adenocarcinoma. During Kaplan-Meier analysis, high HAVCR1 expression in Liver hepatocellular carcinoma and Pancreatic adenocarcinoma correlated with poor survival. A marginally significant p-value (p=0.051) was obtained when the relationship between HAVCR1 expression in Liver hepatocellular carcinoma and prognosis was analyzed, attributed to the small sample size. Overall, we provided compelling evidence that HAVCR1 could be a prognostic and diagnostic marker for Liver hepatocellular carcinoma and Pancreatic adenocarcinoma.